Association Study of Klotho Gene Polymorphism With Calcium Oxalate Stones in The Uyghur Population of Xinjiang, China - Ali, Abdusamat; Tursun, Halmurat; Talat, Alim; Abla, Akpar; Muhtar, Erpan; Zhang, Tao; Mahmut, Murat (Urology Journal, 2017)
Purpose: The aim of the present study was to investigate the correlation between Klotho gene polymorphisms andcalcium oxalate stones in Xinjiang Uyghur people. Materials and Methods: We compared 128 patients with calcium oxalate stones (case group) and 94 healthypeople (control group), detected the genotype and allele distributions of single-nucleotide polymorphisms (SNPs)of the Klotho gene (rs3752472, rs650439, and rs1207568) by reverse transcription polymerase chain reaction. Results: The distributions of the genotype and allele frequencies of the SNPs were consistent with the Hardy-Weinberg equilibrium in the two groups. There were statistically significant differences between the genotype andallele distributions of rs3752472 between the case and control groups; the allele frequencies in the case/controlgroups were C = 240 (93.7%)/151 (80.3%) and T = 16 (6.3%)/37 (19.7%). There was no statistically significantdifference in the genotype distribution of rs650439 between the case and control groups, but there was a differencein the allele distribution; the allele frequencies in the case/control groups were A = 202 (78.9%)/143 (57.2%) andT = 54 (21.1%)/107 (42.8%). There were no statistically significant differences in genotype and allele distributionsbetween the case and control groups of rs1207568; the allele frequencies in the case/control groups were C = 194(71.3%)/145 (77.1%) and T = 78 (28.7%)/43 (22.9%). In rs3752472, the risk for patients with the C and A allelesincreased by 3.675 and 2.799 times, respectively. Conclusion: The rs3752472 and rs650439 SNPs are related to the risk of calcium oxalate stones in Xinjiang Uyghurpeople, and might be one of the risk factors.